2008
DOI: 10.1254/jphs.fp0072385
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Endothelial Nitric Oxide Synthase by Proanthocyanidin-Rich Fraction From Croton celtidifolius (Euphorbiaceae): Involvement of Extracellular Calcium Influx in Rat Thoracic Aorta

Abstract: Abstract. The present study investigates the mechanisms related to the endogenous nitric oxide synthase (eNOS) activation in the relaxant effects of a proanthocyanidin-rich fraction (PRF), obtained from Croton celtidifolius BAILL barks, in rat thoracic aorta rings with endothelium. In vessels pre-contracted with phenylephrine (Phe), PRF (0.1 -100 μg / mL) induced a concentration-dependent relaxation. This effect was significantly reduced by endothelium denudation, by N ω -nitro-L-arginine, and by 1H[1,2,3]oxad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Recent reports regarding the procyanidin-induced relaxation mechanism concluded that relaxation results from hyperpolarization through Ca 2þ -dependent BK Ca 2þ activation. 8,23) By contrast, Kwan et al 9) clearly showed the involvement of vasorelaxant procyanidin-rich extract in the opening of multiple K þ channels including BK Ca 2þ , K V and K ir , consistently with our results. It is likely that whether procyanidins involve the opening of Ca 2þ -dependent or -independent K þ channels or both is dependent on multiple active procyanidins of different origin, since procyandins are heterogeneous condensed tannins of catechins and/or epicatechins.…”
Section: Discussionsupporting
confidence: 91%
“…Recent reports regarding the procyanidin-induced relaxation mechanism concluded that relaxation results from hyperpolarization through Ca 2þ -dependent BK Ca 2þ activation. 8,23) By contrast, Kwan et al 9) clearly showed the involvement of vasorelaxant procyanidin-rich extract in the opening of multiple K þ channels including BK Ca 2þ , K V and K ir , consistently with our results. It is likely that whether procyanidins involve the opening of Ca 2þ -dependent or -independent K þ channels or both is dependent on multiple active procyanidins of different origin, since procyandins are heterogeneous condensed tannins of catechins and/or epicatechins.…”
Section: Discussionsupporting
confidence: 91%
“…A number of animal and human studies have suggested a blood pressurelowering effect of flavonoids from plant sources including soy, red clover, and cocoa (Ding et al, 2006;Howes et al, 2003;Rivas et al, 2002). Vasorelaxing properties of polyphenols appear to be endothelium-dependent and recent studies have strongly suggested that the prime mechanism involves enhanced activation and/or increased expression of endothelial nitric oxide synthase (eNOS) (Appeldoorn et al, 2009;DalBó et al, 2008). Thus, ACE inhibition is not essential for vasorelaxation in agreement with the present study.…”
Section: In Vivo Studysupporting
confidence: 86%
“…We have demonstrated that the PRF presents antinociceptive effects against chemical and thermal noxious stimuli, with involvement of capsaicin‐sensitive C‐fibres and dopamine D 2 receptors [9,10] . Moreover, PRF induces endothelium‐dependent vasorelaxant effects via the NO–cGMP pathway and hyperpolarisation due to the activation of Ca 2+ ‐dependent K + channels in the small‐resistance arteries of rats [11,12] …”
Section: Introductionmentioning
confidence: 94%